France's citizen consultation on vaccination and the challenges of participatory democracy in health. (January 2019) - Ward, Jeremy K.; Cafiero, Florian; Fretigny, Raphael; Colgrove, James; Seror, Valérie
Abstract: Background: Confronted with a rise in vaccine hesitancy, public health officials increasingly try to involve the public in the policy decision-making process to foster consensus and public acceptability. In public debates and citizen consultations tensions can arise between the principles of science and of democracy. To illustrate this, we analyzed the 2016 citizen consultation on vaccination organized in France. This consultation led to the decision to extend mandatory vaccination. Methods: The analysis combines qualitative and quantitative methods. We analyze the organization of the consultation and its reception using the documents provided by its organizing committee, articles of newsmedia and the contents of 299 vaccine-critical websites. Using methods from computational linguistics, we investigate the 10435 public comments posted to the consultation's official website. Results: The combination of a narrow framing of debates (how to restore trust in vaccination and raise vaccination coverages) and a specific organization (latitude was given to the orientation committee with a strong presence of medical experts) was successful in avoiding legitimizing vaccine critical arguments. But these choices have been at the expense of a real reflection on the acceptability of mandatory vaccination and it did not quell vaccine-critical mobilizations. Conclusions: Public health officials must be aware that when trying to increase democratic participation into their decision-making process, how they balance inputs from the various actors and how they frame the discussion determine whether this initiative will provide meaningful information and democratic legitimacy. Highlights: We present the 2016 citizen consultation on vaccination organized in France. We show the tensions at its core between the scientific and democratic principles. We underline the importance of the framing of debates. A missed opportunity to assess the acceptability of vaccine mandates.